Unimolecular reaction dynamics : theory and experiments - Baer, Tomas; Hase, William L. (International series of monographs on chemistry., 1996)
The book provides a penetrating and comprehensive description of energy selected reactions from a theoretical as well as experimental point of view. It presents three major aspects of unimolecular reactions involving the preparation of the reactants in selected energy states, the rate of dissipation of the activated molecule, and the partitioning of the excess energy among the final products.